The in vivo and in vitro corrosion behavior of MgO/Mg-Zn-Ca composite with different Zn/Ca ratio - Zhang, Shuquan; Tang, Chaokun; Feng, Jiangtao; Wang, Qi; Li, Chenguang; Zhang, Weihao; Zhou, Fengxin; Xue, Feng; Xu, Baoshan; Lyu, Shaoyuan; Chen, Minfang; Wang, Hao (Frontiers in Bioengineering and Biotechnology, 2023)
The effect of Zn/Ca ratio on the corrosion behavior of Mg–3Zn-0.2Ca-1.0MgO (3ZX) and Mg–1Zn-0.2Ca-1.0MgO (ZX) was investigated on the as-extruded specimens. Microstructure observations revealed that the low Zn/Ca ratio led to the grain growth from 1.6 µm in 3ZX to 8.1 µm in ZX. At the same time, the low Zn/Ca ratio changed the nature of second phase from the existence of Mg-Zn and Ca2Mg6Zn3 phases in 3ZX to the dominated Ca2Mg6Zn3 phase in ZX. The local galvanic corrosion caused by the excessive potential difference was alleviated obviously due to the missing of MgZn phase in ZX. Besides, the in vivo experiment also showed that ZX composite exhibited a good corrosion performance and the bone tissue around the implant grew well.